THE EFFECT OF LEXICAL COLLOCATION UPON STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT SMAN 4 SINGARAJA IN THE ACADEMIC YEARS 2013/2014 - ., Ni Putu Veni Venikagitayani; ., Dra.Ni Made Ratminingsih, MA; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian Experimen ini bertujuan untuk meneliti efek dari Lexical Collocation pada kemampuan membaca siswa. Untuk melakukan penelitian, 72 siswa telah dipilih sebagai sample. Mereka adalah siswa kelas X MIPA di SMAN 4 Singaraja. Kelompok siswa diberikan lotere, dan hasinya adalah siswa kelas X MIPA 2 terpilih sebagai kelompok Eksperiemen, dan X MIPA 3 sebagai kelompok kontrol. Metode yang digunakan adalah Posttest Only Control Group Design. KElompok Eksperimental diberikan perlakuan berupa Collocation dan kelompok kontrol diberikan perlakuan berupa metode pembelajaran konvensional. Di akhir penelitian, kedua kelompok diberikan post test. Post test yang diberikan berupa tes kemampuan membaca, yang berisi 20 buah test objektif. Data yang didapatkan dianalisis dengan statistik deskriptif dan inferensial. Penelitian ini menggunakan hipotesis alternatif. Hasil dari t test yaitu t observasi lebih tinggi daripada t tabel dengan nilai 2.03, yaitu 5.14. Dari hasil ini, hipotesis nol ditolak dan hipotesis alternatif diterima. Hipotesis nol yang ditolak berarti ada perbedaan yang signifikan antara siswa yang diajarkan dengan Lexical Collocation dan yang tidak.Kata Kunci : Lexical Collocation, Pembelajaran membaca konvensional, kemampuan membaca. This experimental research aimed at investigating the effect of Lexical Collocation on students’ reading comprehension achievement. To conduct the research, 72 students were selected as the samples. They were the tenth grade students of science major at SMAN 4 Singaraja. The group of students were given the lottery, and the result showed that the X MIPA 2 was experimental group and X MIPA 3 was the control group. The design used in this research was Post Test Only Control Group Design. The experimental group was given collocation as treatment and the control group was taught by using a conventional teaching method. At the end, both experimental and control groups were given the post test. The post test was a reading comprehension test, consist of 20 multiple choices. The data obtained by the post test were analyzed by using Descriptive and Inferential Statistic Analyses. This study used alternative hypothesis. The result of t test in which t observed was higher than t critical value 2.03 was 5.14. Based on the result, the null hypothesis was rejected and the alternative hypothesis was accepted. The rejected null hypothesis means that there is significant difference on reading comprehension between the students who were taught by using collocation and who were not. keyword : Lexical Collocation, Conventional teaching reading, Reading comprehension